2019
DOI: 10.4103/ijo.ijo_2151_18
|View full text |Cite
|
Sign up to set email alerts
|

Eye donation in north India: Trends, awareness, influences and barriers

Abstract: Purpose:To understand trends, awareness, influences and barriers to eye donation in Indian society.Methods:This cross sectional study was conducted in Delhi from March 2017 to February 2018. About 10 hospitals collaborated with the Eye Bank under Human Cornea Retrieval Program (HCRP). Eye Bank recruited Eye Donation Counselors (EDCs) to approach family members of the deceased. A pretested questionnaire was used for this study. Irrespective of whether the next of kin of the deceased consented for eye donation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 14 publications
3
30
1
Order By: Relevance
“…Other sources included newspaper, family members, neighbors etc. Source of motivation for corneal donation was counselling in a study by Acharya, et al in which about 41% participants were willing to donate cornea after counselling [13]. Sharma, et al in their study observed 61 (57.5%) cases where the willingness come post direct motivation by grief counselors [6].…”
Section: Discussionmentioning
confidence: 99%
“…Other sources included newspaper, family members, neighbors etc. Source of motivation for corneal donation was counselling in a study by Acharya, et al in which about 41% participants were willing to donate cornea after counselling [13]. Sharma, et al in their study observed 61 (57.5%) cases where the willingness come post direct motivation by grief counselors [6].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common issues is related to the concern of disfigurement following corneal donation. 9, 10 Another important barrier to corneal donation is the lack of awareness and knowledge of corneal donation amongst the general public. 10-12 In addition, staff may feel uncomfortable or unconfident in discussing corneal donation with the patients and the relatives.…”
Section: Introductionmentioning
confidence: 99%
“…9, 10 Another important barrier to corneal donation is the lack of awareness and knowledge of corneal donation amongst the general public. 10-12 In addition, staff may feel uncomfortable or unconfident in discussing corneal donation with the patients and the relatives. 13 To address the constant deficit of donor corneas, various countries have considered and implemented a range of initiatives and research programmes, including campaigns to increase public awareness of corneal donation, introduction of telephone consent, refinement in the eye retrieval and eye banking systems, and development of corneal cell-based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The success rates for eye donation following counseling as per an Indian study ranges between 30 and 40%. [ 5 ] For plasma donation, the success rate of 32% was achieved following counselling (91 + 58 cases of the 460 eligible donors counseled). Lower figures could be attributed to the newer arena for eye bank counselors and an early evaluation.…”
mentioning
confidence: 99%